Shear Behavior of A325 and A490 High-Strength Bolts in Fire and Post-Fire - Yu, Liang; Frank, Karl H. (Engineering Journal, 2009)
High strength ASTM A325 and A490 bolts were tested in shear at temperatures up to 800 °C (1,472 °F). The shear strength showed a gradual reduction in both types of bolts as the temperature was increased above 300 °C (572 °F). Strength reduction factors for both types of bolts at elevated temperatures were obtained to provide a means of estimating the bolt shear strength during fire. The residual strength of A325 and A490 bolts after exposure to elevated temperatures was also investigated by both direct shear tests and hardness tests. Significant strength loss occurs on both types of bolts after exposure to temperature higher than the tempering temperature employed in the manufacturing process. The hardness value at 1/2R location on the bolt cross section was found to provide a good estimate of the bolts residual strength. The hardness test provides a simple and practical method to assess the post fire strength of a bolt.